A method for preparing cyclic carbonate by addition reaction of CO2 and epoxide
Through the covalent connection technology of bridged metalporphyrin catalysts, the problem of insufficient catalyst stability and catalytic activity in the prior art is solved, and a method for efficient preparation of cyclic carbonate is realized, with high catalytic activity, low metal content and high heat Advantages of stability and other advantages.
Patent Information
- Application Number
- CN202411559466.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the prior art, when catalyzing the addition of CO2 and epoxides to prepare cyclic carbonates, the stability and catalytic activity of the catalyst are insufficient, and the preparation process requires high-temperature roasting and consumes a large amount of energy.
A bridged metalporphyrin catalyst is used to form a catalytic system with better stability through covalent connection, catalyzing the addition reaction of CO2 and epoxide to prepare cyclic carbonate. The catalyst is prepared by covalent linking of urethane groups by hydroxy-substituted porphyrin and isocyanate as a bridge agent.
It realizes efficient reuse of catalysts, with low metal content in cyclic carbonates, no heavy metals, high catalytic activity, strong selectivity, high thermal stability, simple process and convenient operation.
Smart Images

Figure CN119060010B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing cyclic carbonate by heterogeneous catalysis of CO2, in particular to a method for preparing cyclic carbonate by catalyzing CO2 and epoxide by bridged metal porphyrin; the invention belongs to the technical field of organic synthesis. Background Art
[0002] Carbon dioxide is a greenhouse gas with extremely high emissions and is also a cheap and readily available C1 resource. Converting CO2 into high-value-added chemicals can not only alleviate greenhouse gas emissions, but also provide a sustainable path for chemical preparation. Among all CO2 fixation strategies, the cycloaddition of CO2 with epoxides to form cyclic carbonates and their analogues is considered to be one of the most promising methods because it has the advantages of high atom economy (100%), more environmental protection and a variety of structures, which can be further converted into a variety of fine chemicals to create good economic benefits.
[0003] The synthesis of cyclic carbonates using CO2 as raw material can fix CO2 for a long time, which meets the requirements of green and environmentally friendly chemistry. Therefore, the catalytic conversion of CO2 into fuels and chemicals is of great significance for the realization of carbon neutrality goals. Among the many reaction pathways, the reaction of CO2 with epoxides to form cyclic carbonates is a highly concerned atom-economic pathway.
[0004] CN114478463A discloses an application of SAPO-34 molecular sieve as a catalyst for the preparation of cyclic carbonates by the cycloaddition of carbon dioxide to epichlorohydrin. The scheme uses Zn-doped SAPO-34 molecular sieve as a catalyst to achieve the preparation of cyclic carbonates; however, the catalyst preparation comprises mixing an aluminum source, a zinc source, a phosphorus source and water, performing a first reaction, and then adding silica sol to perform a second reaction to obtain a Si-Al-P mixed sol; SAPO-34 seed crystals and a template agent are then added, and the obtained mixed solution is sequentially crystallized and calcined to obtain the Zn-doped SAPO-34 molecular sieve. The preparation of the catalyst requires high-temperature calcination above 500°C, which consumes a large amount of energy.
[0005] Since there are four N atoms coordinated with various metal atoms (ions) in the center of the porphyrin molecule cavity, the two H atoms on the porphyrin ring are replaced by metal atoms (ions) to form a stable metal porphyrin compound, which can activate molecular oxygen under mild conditions and show high catalytic activity and selectivity in catalytic oxidation reactions. Therefore, the use of metal porphyrin compounds to catalyze CO2 as a raw material to synthesize cyclic carbonates has become a research hotspot. For example, CN112480059A discloses a method for directly synthesizing cyclic carbonates from olefins catalyzed by metal porphyrins, which uses metal porphyrins as catalysts and ionic liquids as co-catalysts to catalyze olefins, carbon dioxide and oxidants for epoxidation carboxylation reactions, and prepares cyclic carbonates in one pot. The catalyst used in this method is easy to decompose.
[0006] Therefore, it is particularly necessary to develop a catalytic system with better stability and higher catalytic activity to catalyze the addition reaction of CO2 and epoxide. Summary of the invention
[0007] In view of the above-mentioned shortcomings, the purpose of the present invention is to develop a method for preparing cyclic carbonates by catalyzing the addition of CO2 and epoxides by polymerizing monometallic porphyrins into a covalent metal porphyrin catalytic system with better stability and higher catalytic activity through a bridging agent.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing cyclic carbonate by addition reaction of CO2 and epoxide, comprising adding a bridged metal porphyrin catalyst and epoxide into a high-pressure reactor, introducing CO2 until the reaction pressure reaches 1.0 MPa, sealing the reactor, and reacting at 80-160° C. for 12-48 hours to obtain a cyclic carbonate;
[0010] The structure of the bridged metal porphyrin is shown in the following general formula (I):
[0011]
[0012] Formula (I);
[0013] Wherein: M is one of Zn, Co, Cu, Fe, Mn and Al;
[0014] R is .
[0015] Furthermore, in the above-mentioned method for preparing cyclic carbonate by addition reaction of CO2 and epoxide, the auxiliary agent is one of tetrabutylammonium bromide, benzyltriethylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride.
[0016] Furthermore, in the above-mentioned method for preparing cyclic carbonate by addition reaction of CO2 and epoxide, the molar ratio of the epoxide to the catalyst is 400-4000:1.
[0017] Furthermore, in the above-mentioned method for preparing cyclic carbonate by addition reaction of CO2 and epoxide, the molar ratio of the auxiliary agent to the catalyst is 1-10:1.
[0018] Furthermore, in the above-mentioned method for preparing cyclic carbonate by addition reaction of CO2 and epoxide, the epoxide is one of epichlorohydrin, ethylene oxide, propylene oxide, 1,2-butylene oxide, and 1,4-butylene oxide.
[0019] Furthermore, in the above-mentioned method for preparing cyclic carbonate by addition reaction of CO2 and epoxide, the bridged metal porphyrin is prepared by the following method: hydroxy-substituted porphyrin is used as the main raw material, isocyanate is used as the bridging agent, a porphyrin polymer [(Por)POP] is prepared by covalently linking the amino ester group, and then a metal halogenating agent is added to prepare a bridged metal porphyrin polymer [M(Por)POP].
[0020] Compared with the prior art, it has the following beneficial effects:
[0021] (1) The catalyst used in the present invention is a bridged metal porphyrin porous material, the catalyst can be reused, and the metal content in the subsequent cyclic carbonate is low and does not contain heavy metals;
[0022] (2) The present invention uses bridged metal porphyrin porous material catalysis, the yield of cyclic carbonate is high, the catalyst has high catalytic activity, strong selectivity and high thermal stability;
[0023] (3) The present invention adopts gas-liquid phase addition reaction, the product and the catalyst are easy to separate, the operation is convenient, safe and efficient, and the process is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the SEM image of the catalyst Zn(Por)POP;
[0025] Figure 2 is the XRD pattern of catalyst Zn(Por)POP;
[0026] Figure 3 FT-IR images of (Por)PO and Zn(Por)POP;
[0027] Figure 4 XPS patterns of (Por)PO and Zn(Por)POP;
[0028] Figure 5 TG diagrams of (Por)PO and Zn(Por)POP;
[0029] Figure 6 is the nitrogen adsorption and desorption isotherms of Zn(Por)POP;
[0030] Figure 7 This is the pore size distribution diagram of Zn(Por)POP based on the NLDFT method. DETAILED DESCRIPTION
[0031] The present invention is further described in the following examples, but these examples are for illustrative purposes only and should not be construed as limiting the implementation of the present invention.
[0032] Example 1
[0033] In a 10mL stainless steel high-pressure reactor, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and the reaction was carried out by slowly purging with CO2 for 3 times at room temperature and then injecting 1.0Mpa CO2. The reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 84.1%.
[0034] Example 2
[0035] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 1.0Mpa CO2 was injected after slowly purging with CO2 at room temperature for 3 times, and then sealed, and stirred at 200r / min in a constant temperature oil bath at 120°C for 16h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 87.5%.
[0036] Example 3
[0037] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 1.0Mpa CO2 was injected after slowly purging with CO2 for 3 times at room temperature, and then sealed, and stirred at 200r / min in a constant temperature oil bath at 120°C for 24h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 92.3%.
[0038] Example 4
[0039] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 1.0Mpa CO2 was injected after slowly purging with CO2 for 3 times at room temperature, and then sealed, and stirred at 200r / min in a constant temperature oil bath at 120°C for 48h. After the reaction, the autoclave was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 93.6%.
[0040] Example 5
[0041] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 3mg of TBAB cocatalyst was added. After slowly purging with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 91.1%.
[0042] Example 6
[0043] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 8mg of TBAB cocatalyst was added. After slowly ventilating with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 94.7%.
[0044] Example 7
[0045] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 10mg of TBAB cocatalyst was added. After slowly ventilating with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 16h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 97.8%.
[0046] Example 8
[0047] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 4mg of TBAB co-catalyst was added. After slowly purging with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 160°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 99.1%.
[0048] Example 9
[0049] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 1mg of TBAB cocatalyst was added. After slowly purging with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 80°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 83.5%.
[0050] Example 10
[0051] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 5mg of TBAB co-catalyst was added. After slowly purging with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 80°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 93.9%.
[0052] Embodiment 11
[0053] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst cobalt porphyrin polymer catalyst Co(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 5mg of TBAB cocatalyst was added. After slowly ventilating with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 95.8%.
[0054] Example 12
[0055] In a 10mL stainless steel autoclave, 20mg of bridged catalyst copper porphyrin polymer catalyst Cu(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 5mg of TBAB cocatalyst was added. After slowly ventilating with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 87.1%.
[0056] Example 13
[0057] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst Fe(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 5mg of TBAB was added as a cocatalyst. After slowly purging with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 82.6%.
[0058] Embodiment 14
[0059] In a 10mL stainless steel autoclave, 20mg of bridged catalyst aluminum porphyrin polymer catalyst Al(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 5mg of TBAB cocatalyst was added. After slowly ventilating with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, sealed, and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 88.6%.
[0060] Comparative Example 1
[0061] In a 10mL stainless steel autoclave, 20mg of porphyrin polymer catalyst (Por) POP and 278mg (3mmol) of epichlorohydrin were added, and 5mg of TBAB cocatalyst was added. After slowly ventilating with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 53.7%.
[0062] Comparative Example 2
[0063] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Mn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and 5mg of TBAB cocatalyst was added. After slowly purging with CO2 for 3 times at room temperature, 1.0Mpa CO2 was injected, and the reaction was sealed and stirred at 200r / min in a constant temperature oil bath at 120°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 78.2%.
[0064] Comparative Example 3
[0065] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and CO2 was slowly ventilated 3 times at room temperature, and then 1.0Mpa CO2 was injected, sealed, and stirred at 200r / min in a constant temperature oil bath at 80°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 75.7%.
[0066] Comparative Example 4
[0067] In a 10mL stainless steel autoclave, 20mg of the bridged catalyst zinc porphyrin polymer catalyst Zn(Por)POP and 278mg (3mmol) of epichlorohydrin were added, and CO2 was slowly ventilated 3 times at room temperature, and then 1.0Mpa CO2 was injected, sealed, and stirred at 200r / min in a constant temperature oil bath at 100°C for 12h. After the reaction, the reactor was cooled to below room temperature with ice water, and the excess CO2 was slowly released. The filtrate was diluted with 5mL of biphenyl ethyl acetate solution, and the yield of cyclic carbonate was 78.2%.
[0068] The bridged catalyst zinc porphyrin polymer catalyst involved in the examples and comparative examples is prepared by the following reaction formula:
[0069]
[0070] The specific preparation method is as follows:
[0071] 100 mg (0.15 mmol) of 5, 10, 15, 20-tetrakis (4-hydroxyphenyl) porphyrin and 118 mg (0.45 mmol) of dicyclohexylmethane 4, 4-diisocyanate were added to a 50 mL Schlenk tube, and then 10 mL of anhydrous butanone was added to dissolve the mixture and stirred at 800 r / min for 48 h under a nitrogen atmosphere. After the reaction, the solution was centrifuged at 8000 r / min for 10 min, filtered, and the filter cake was washed with tetrahydrofuran and methanol respectively and dried in a vacuum drying oven at 80 ° C for 12 h to obtain a purple-black solid [(Por)POP].
[0072] Add 250 mg (0.21 mmol) [(Por)POP], 10 mL acetonitrile and 0.6 mL anhydrous triethylamine to a 50 mL Schlenk tube, stir evenly, then add 5 mL zinc bromide (135 mg, 0.6 mmol) acetonitrile solution, and stir in a constant temperature oil bath at 80°C at 800 r / min for 12 h. After the reaction, the solution was cooled to room temperature, filtered through an organic filter membrane on a 60 mL Buchner funnel to obtain a filter cake, which was washed with methanol, tetrahydrofuran and acetone, respectively. The wet filter cake was transferred to a Soxhlet extractor, extracted with tetrahydrofuran and acetone for 12 h, and then dried in a vacuum drying oven at 80°C for 12 h to obtain a black solid Zn(Por)POP.
[0073] The preparation methods of Fe(Por)POP, Mn(Por)POP, Al(Por)POP and Co(Por)POP are basically the same as those of Zn(Por)POP, except that an equimolar amount of copper chloride or manganese bromide or aluminum chloride or cobalt chloride is used instead of zinc bromide.
[0074] In order to prove the catalyst provided by the present application, the detection spectrum of the catalyst provided by the present application is given below, wherein the SEM image of the catalyst Zn(Por)POP is shown in Figure 1 , XRD pattern of catalyst Zn(Por)POP can be found at Figure 2 , (Por)PO and Zn(Por)POP FT-IR images are available at Figure 3 , (Por)PO and Zn(Por)POP XPS charts refer to Figure 4 TG diagrams of (Por)PO and Zn(Por)POP are shown in Figure 5 , nitrogen adsorption and desorption isotherms of Zn(Por)POP are shown in Figure 6 ; See the pore size distribution diagram of Zn(Por)POP based on NLDFT method Figure 7 .
[0075] from Figure 1It can be seen that the Zn(Por)POP catalyst has uniform particle size distribution and good dispersibility; Figure 2 The results show that Zn(Por)POP has a typical crystal structure with sharp diffraction peaks, indicating that it has good crystallinity. Figure 3 The FT-IR graph shown further reveals that there is a strong coordination effect between (Por)PO and Zn ions. Figure 4 It can be seen that the valence state and distribution of Zn element; TG Figure 5 The stability of Zn(Por)POP during heating is shown in the nitrogen adsorption-desorption isotherm of Zn(Por)POP. Figure 6 And the pore size distribution of Zn(Por)POP based on NLDFT method Figure 7 The results show that Zn(Por)POP has a large specific surface area and pore volume, which is beneficial to the catalytic reaction.
Claims
1. A method for preparing cyclic carbonate by addition reaction of CO2 and epoxide, characterized in that: Add a bridged metal porphyrin catalyst and epoxide to a high-pressure reactor, introduce CO2 until the reaction pressure reaches 1.0 MPa, seal the reactor, and react at 80-160° C. for 12-48 hours to obtain a cyclic carbonate; The structure of the bridged metal porphyrin is shown below (I): Wherein: M is one of Zn, Co, Cu, Fe, Mn and Al; R are: The epoxide is one of epichlorohydrin, ethylene oxide, propylene oxide, 1,2-butylene oxide and 1,4-butylene oxide.
2. The method for preparing cyclic carbonate by addition reaction of CO2 and epoxide according to claim 1, characterized in that: A promoter is also added into the high-pressure reaction kettle.
3. The method for preparing cyclic carbonate by addition reaction of CO2 and epoxide according to claim 2, characterized in that: The co-catalyst is one of tetrabutylammonium bromide, benzyltriethylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride and tetradecyltrimethylammonium chloride.
4. The method for preparing cyclic carbonate by addition reaction of CO2 and epoxide according to claim 1, characterized in that: The molar ratio of the epoxide to the catalyst is 400-4000:
1.
5. The method for preparing cyclic carbonate by addition reaction of CO2 and epoxide according to claim 3, characterized in that: The molar ratio of the co-catalyst to the catalyst is 1-10:
1.
6. The method for preparing cyclic carbonate by addition reaction of CO2 and epoxide according to claim 1, characterized in that: The bridged metalloporphyrin is prepared by the following method: Hydroxyl-substituted porphyrin is used as the main raw material, isocyanate is used as the bridging agent, and the porphyrin polymer [(Por)POP] is prepared by covalently linking the urethane group, and then a metal halide is added to prepare a bridged metal porphyrin polymer [M(Por)POP; The hydroxy-substituted porphyrin is 5,10,15,20-tetrakis(4-hydroxyphenyl)porphyrin; The isocyanate is dicyclohexylmethane 4,4-diisocyanate; The metal halogenating agent is one of zinc bromide, copper chloride, manganese bromide, aluminum chloride, and cobalt chloride; The porphyrin polymer structural formula is as follows: R are:
Citation Information
Patent Citations
Method for directly synthesizing cyclic carbonate from olefin under catalysis of metalloporphyrin
CN112480059A
Method for preparing cyclic carbonate by transforming carbon dioxide with chromium-based catalyst
CN107805239A
Porous metalloporphyrin polymer containing benzimidazole ionic liquid, preparation method and application thereof
CN113912843A